Tinjauan Yuridis Konsepsi Hak Langgeh dalam Masyarakat Tradisional Hukum Adat Aceh - Nila Trisna; Ilka Sandela; Adam Sani (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Recognition of the traditional rights of the community, such as the implementation of traditional and cultural life which differs from one region to another, is the glue of the Unitary State of the Republic of Indonesia. One of them is the customs and culture that exist in society in Aceh, namely Langgeh Rights. Langgeh rights are former rights, namely the right of one person is more important than others, to get the opportunity to buy the neighbor's land at the same price. Langgeh rights can be given to the closest person to the seller, namely, relatives of the seller, other members of customary law, or neighbors whose land is directly sold with the land to be sold. Langgeh rights aim to prevent the land from being purchased by foreigners from outside the customary law community. In practice, the settlement of disputes over the rights of langgeh (syuf'ah) in Aceh almost entirely cannot be resolved through the Syari'ah Court, but will be resolved in the gampong customary court, this is because the Acehnese are a society that upholds the Shari'ah who expect peace. They do not expect mutual hostility, so the outcome of the customary justice process is peace.